A revision of Megagraphydrus Hansen (Coleoptera, Hydrophilidae): synonymization with Agraphydrus Régimbart and description of seven new species - Minoshima, Yûsuke N.; Komarek, Albrecht; Ôhara, Masahiro (Zootaxa, 2015)
The genus Megagraphydrus Hansen, 1999 is revised. Eleven of the twelve previously described species are recognized as valid, with Megagraphydrus wangi Hebauer, 2000 syn. nov. found to be a junior synonym of M. politus Hansen, 1999. Most significantly, Megagraphydrus itself is found to be a junior synonym of Agraphydrus Régimbart, 1903. The species are assigned to the subgenus Agraphydrus. This nomenclatural act results in the following new combinations: Agraphydrus (Agraphydrus) anhuianus (Hebauer, 2000) comb. nov., A. (A.) attenuatus (Hansen, 1999) comb. nov., A. (A.) jaechi (Hansen, 1999) comb. nov., A. (A.) luteilateralis (Minoshima & Fujiwara, 2009) comb. nov., A. (A.) malayanus (Hebauer, 2000) comb. nov., A. (A.) politus (Hansen, 1999) comb. nov., A. (A.) puzhelongi (Jia, 2010) comb. nov., A. (A.) regularis (Hansen, 1999) comb. nov., A. (A.) siamensis (Hansen, 1999) comb. nov., A. (A.) superans (Hebauer, 2000) comb. nov., and A. (A.) uvaensis (Hebauer, 2000) comb. nov. All species are redescribed with the exclusion of A. superans, A. luteilateralis, and A. puzhelongi. Seven new species are described: Agraphydrus (Agraphydrus) biprojectus sp. nov., A. (A.) coronarius sp. nov., A. (A.) decipiens sp. nov., A. (A.) insidiator sp. nov., A. (A.) masatakai sp. nov., A. (A.) montanus sp. nov., A. (A.) thaiensis sp. nov. Digital and SEM photographs are provided, and the male and female genital segments are illustrated and described.